Response: Anxiety and behaviour in and beyond ASD; does the idea of 'PDA' really help? – a response to Green (2020). Issue 2 (27th March 2020) - Grahame, Victoria; Stuart, Lisa; Honey, Emma; Freeston, Mark
Abstract : We acknowledge Green's viewpoint and agree that currently the literature does not support the validity of PDA as an independent syndrome. However, the controversy is real and exists for a reason. We therefore argue that it is important to move beyond labelling and the potentially unhelpful implications of discussion around whether or not it is a condition, diagnosis or a co‐morbid condition, to a point of recognition of the phenomenon. We argue that what we need is more accurate description of these behaviours and better measurement to allow us to answer key questions about this phenomenon, whatever we name it. In our paper (Stuart et al, Child and Adolescent Mental Health, 2019) and response, we are trying to move the debate on from opinion and anecdote to be more data‐driven, which hopefully leads to increased identification of what research needs to be done. We build on this argument by outlining our second proposed and yet to be published paper exploring the role that IU has in the relationship between ASD, PDA (however we label this) and anxiety. Abstract : Read the commentary at doi: 10.1111/camh.12379 and full article at doi: 10.1111/camh.12336